Principle of balance in financial technology’s peer-to-peer lending contract - Indah Siti Aprilia; Claudia Gita Hapsari (IDEAS: Journal of Management & Technology, 2021)
Online loans have snowballed in recent years. The growth of online loans, also known as Peer-to-Peer Lending (P2P Lending) or Financial Technology, has been troubling the public. The P2P Lending collecting method has been harassing the people. P2P lending sends the collection letter to customers' contact addresses, distributes personal pictures, and imposes high interest. This research aims to discuss the Principle of Balance in P2P Lending contracts. This research uses a normative judicial method. The study examines the phenomenon of P2P Lending in public. This research concludes that the P2P Lending agreement does not meet the conditions in the contract based on the Principle of Balance. This research proposes that the relevant authorities review each P2P Lending agreement to achieve the Principle of Balance.